Mathematics in ancient Jaina literature - Jain, Anupam; Dani, Shrikrishna (Singapore: World Scientific, 2024)
"A collection of articles on the mathematical concepts and knowledge found in ancient and medieval Jaina literature. Contains articles related development of ideas concerning arithmetic and geometry in the Jaina tradition, specific themes that engaged Jaina scholars, and connections to modern topics like cryptography and logic in statistical thinking"--
Includes bibliographical references.
Keywords: Jaina mathematics; Mathematics, Ancient -- India; Mathematics, Medieval -- India